Tobacco Drying Mechanism Study of Temperature and Heat Physics - Kholifatus Amaliah; Trapsilo Prihandono; Sudarti Sudarti (Department of Physics Education, Universitas Mataram, 2022)
We find many applications of physics in everyday life, ranging from simple things to complex things. One example of the application of physics in everyday life is the activity of drying tobacco, when in its management there are concepts of temperature and heat. This study aims to examine the mechanism of drying tobacco based on the concept of heat which can later be integrated into the physics learning. The research method consists of observation, interviews, and documentation. The data analysis stage in this study consisted of data reduction, data presentation, and conclusions. The results showed that in the tobacco drying mechanism there is a conduction heat transfer process during the fire curing and convection heat transfer process during the air curing in the drying warehouse and radiation heat transfer in sun drying. Due to the transfer of heat into the tobacco causes evaporation so that the water content in the tobacco is reduced. The factors that cause evaporation are difference in temperature, wind, humidity, cross-sectional area, and air pressure.